CREATIVE STORY THROUGH 9GAG APPLICATION IN TEACHING SPEAKING - Tsamara Fairuz Suni (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2021)
This study aims to improve students’ speaking abilities trough creative story in 9GAG application. The method used in research is a quantitative method with Quasi Experimental as a research design. Both pre-test and post-test used as the instruments in collecting the data. The writer used two classes of ninth grade of MTs Al-Islamiyah, Tangerang for the population. The sampling technique used was cluster sampling in which 9.4 was determined as experimental class and 9.5 as the control class. The data was analyzed statistically by using t-test. The result of this analysis indicated that the average value of the students was 70.33, the statistical calculation showed that the results of to (t-observation)> tt (t-table) in which to obtained was 19.24 while the value of tt was 2.015 with a significant level of 5% (0.05), since, to was higher than tt, therefore alternative hypothesis (Ha) was accepted while null hypothesis was rejected. From these analysis results, this research summarized that 9GAG Application was an effective media to improve students’ speaking skill.